Voorzitterswisseling. Van rechts naar links: Jansen, Wiersma en Snoeck. Serie van 2 foto's - Dijk, David van
Voorzitterswisseling. Van rechts naar links: Jansen, Wiersma en Snoeck. Serie van 2 foto's.